2022
DOI: 10.3389/fmed.2022.905131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sugammadex and Neostigmine on Post-operative Nausea and Vomiting in ENT Surgery

Abstract: We aim to compare the effects of sugammadex on postoperative nausea and vomiting (PONV) with those of neostigmine–atropine mixture. A total of 136 American Society of Anesthesiology (ASA) I or II patients, aged 18 to 65 years who underwent ear, nose, and throat (ENT) surgery under general anesthesia, were recruited in this prospective, randomized, double-blind study to receive either sugammadex 2 mg/kg or neostigmine 2.5 mg with atropine 1 mg for reversal of neuromuscular blockade. PONV scores and the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…37 However, subsequent small studies have demonstrated reduction in PONV with sugammadex within the first 6 hours postoperatively compared to CI. 38,39 In our review, no study recorded PONV at different time points to elucidate temporal differences. This could suggest that differences in PONV are likely a function of CI avoidance rather than a benefit of sugammadex, with muscarinic effects of CI diminishing overtime leading to no difference in PONV after 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…37 However, subsequent small studies have demonstrated reduction in PONV with sugammadex within the first 6 hours postoperatively compared to CI. 38,39 In our review, no study recorded PONV at different time points to elucidate temporal differences. This could suggest that differences in PONV are likely a function of CI avoidance rather than a benefit of sugammadex, with muscarinic effects of CI diminishing overtime leading to no difference in PONV after 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many anesthesiologists choose to use antagonists at the end of surgery to avoid residual neuromuscular blockade, and the commonly used antagonists are neostigmine and sugammadex. The combination of neostigmine and atropine has been associated with postoperative nausea and vomiting, pneumonia and respiratory failure [13,14], and although sugammadex are preferred for their advantages [15]. In the absence of quantitative neuromuscular monitoring however, there is uncertainty as to whether an antagonist is required and whether the antagonist dose is fully antagonised.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies exploring the effects of sugammadex on PONV, most of the available evidence suggests that sugammadex only tends to reduce the occurrence of PONV; however, these results failed to reach statistical significance [ 9 , 10 ]. In addition, most of the possible explanations for the relationship between sugammadex and reduction in PONV focuses on the emetic effect of neostigmine [ 11 ]. Whether sugammadex use is related to the decreased occurrence of PONV during inpatient hospitalization, which is critical for the rehabilitation of patients undergoing bariatric surgery, remains unknown.…”
Section: Introductionmentioning
confidence: 99%